Land Finance and fiscal rules: An estimated DSGE model for Hong Kong - Wenwen Zhang; Zongyi Liu (PLoS ONE, 2026)
This study systematically analyzes the choice of fiscal rules under Hong Kong’s land finance pattern and their macroeconomic implications for the first time through DSGE methods. Using quarterly data from 2000 Q1 to 2023 Q4, we employs Bayesian estimation and simulation to compare the effects of three fiscal rules: the fully exogenous rule, the output-responsive rule, and the debt-responsive rule. Results indicate that the debt-responsive rule delivers optimal outcomes in stabilizing consumption, investment, and labor markets. It effectively curbs pressures from rising government debt and property prices while enhancing fiscal sustainability. Welfare comparison results similarly confirm the superiority of the debt-responsive rule over the other two policies. Variance decomposition reveals that stamp duty shocks constitute the primary fiscal source of Hong Kong’s macroeconomic fluctuations, exerting significant impacts particularly on net exports, labor markets, and the government debt-to-revenue ratio. The conclusions of this study hold significant policy implications for Hong Kong and other economies with similar characteristics.